A Class of Distributions Defined by Quantile Density Function. Issue 1 (March 2014) - Midhu, N.N.; Sankaran, P.G.
Abtsrcat: In the present paper, we introduce and study a class of distributions that has simple quantile density function. Various distributional properties and reliability characteristics of the class are studied. The method of L-moments is employed to estimate parameters of the proposed class of distributions. Finally, we apply the proposed class to two real data sets.